Utilization of Solar Panels To Distribute Clean Water In Saibi Samukop Village - Rahmad Samosir; Berlianto Daud Immanuel; Medyawanti Pane (VANOS Journal of Mechanical Engineering Education, 2022)
Water as one of the important elements of life is a problem in its availability in nature. The availability of water used is only 3% fresh water compared to seawater. Saibi Samukop Village is a village located in the Mentawai Islands with minimal development including the construction of a clean water supply for community needs. To obtain clean water easily, the researchers designed a clean water distribution system by utilizing solar energy as an energy source to drive DC pumps. 2 solar panels used 100 Wp to charge 2 batteries as power storage. The pump specifications used have a maximum power of 180 Watts with a 15 meter Head with 12 Volts. From the test results an 8.1 pump head operating for 6,4 hours/day with a required power of 100,5 Watt and an electric current of 53,6 Ah. The pump is able to distribute water to the Pangasaat hamlet community in the range of 100,50 liters/day.